ACTUAL PAY, POSITIVE AFFECT (PA), AND PAY SATISFACTION: TEST OF SIGNAL SENSITIVITY PERSPECTIVE - Zaky, Muhammad; Handoko, Hani; Ali, Zakiyulfikri (Universitas Brawijaya, Indonesia, 2018)
This research aims to determine the effect of actual pay level, positive affect (PA) and multi-dimensional pay satisfaction. The data is collected from questionnaires distributed to 207 postgraduate students in Jakarta and Yogyakarta. Non-probability sampling with Purposive sampling is taken as a sampling technique. Hierarchical regressions analysis used for hypothesis testing. The finding shows actual pay level has the positive effect with each pay satisfaction dimension. Positive affect has the positive effect with each pay satisfaction dimension. More importantly, data show that positive affect (PA) interact with actual pay level in explaining three pay satisfaction dimensions, they are satisfied with pay level, satisfaction with benefit, and satisfaction with structure/administration. The finding also shows that positive affect (PA) does not moderate the relation of actual pay level and pay satisfaction on satisfaction with pay raise dimension. Discussion, limitations, a practical and theoretical implication for further researches are offered.